CHINESE HERBAL DECOCTION AS A COMPLEMENTARY THERAPY FOR ATROPHIC GASTRITIS: A SYSTEMATIC REVIEW AND META-ANALYSIS - Fang, Wen-jie; Zhang, Xin-ying; Yang, Bo; Shu-jing, Su; Chen, Min; Wei-hua, Pan; Wan-qing, Liao; Zhong, Ming; Wang, Qing-cai (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Chinese herbal decoction (CHD) has been extensively used in the treatment of atrophic gastritis (AG) in China and other Far Eastern countries. We conducted a systematic review and meta-analysis to estimate the efficacy and safety of CHD in AG.Materials and Methods: Pubmed, Embase, Cochrane central register of controlled trials (central), VIP, China National Knowledge Infrastructure, Sinomed, Wanfang data were searched (up to December 2015). Randomized controlled trials recruiting patients with AG comparing CHD (alone or with western medicine (WM)) with WM were eligible. Dichotomous data were pooled to obtain relative risk (RR), with a 95% confidence interval (CI).Results: Forty-two articles including 3,874 patients were identified. CHD, used alone or with WM, had beneficial effect over WM in the improvement of clinical manifestations (RR=1.28; 95% CI 1.22-1.34) and pathological change (RR=1.42; 95% CI 1.30-1.54) for AG patients. However, the H. pylori eradication effect of CHD was not supported by the existing clinical evidence, because of the significant study heterogeneity (I2>50%) and inconsistency between the primary results and sensitivity analysis.Conclusions: CHD, if prescribed as a complementary therapy to WM, may improve the clinical manifestations and pathological change for AG patients. But its monotherapy for H. pylori eradication is not supported by enough clinical evidence.